The Effect of Using Everyone's Strategy to Become a Teacher for Students' Confidence in Learning Mathematics in Grade 5 Elementary School Students: Pengaruh Penggunaan Strategi Setiap Orang Menjadi Guru Bagi Kepercayaan Diri Siswa dalam Pembelajaran Matematika pada Siswa Kelas 5 Sekolah Dasar - Hariyati, Wahyuni; Efendi, Nur (Indonesian Journal of Education Methods Development, 2022)
Based on the interviews and data that the researchers conducted it can be seen that many students have difficulty understanding the mathematics material presented by the teacher, besides that student lack self-confidence in learning mathematics. Therefore this research was conducted aiming to increase students confidence in learning mathematics by using the everyone is a teacher here strategy. This research uses the Pre-Experimental Design (nondesign) research method. With the design of Intact-Group Comparison reseachers. In this study, researchers used a questionnaire post to determine students confidence in learning mathematics using the everyone is a teacher here strategy. The questionnaire used amounted to 12 statements. The sample used was 2 classes, namely class IV-C as a control class with 30 students and class IV-D as an experimental class with 30 students. Data analysis using the independent sample Test t test and Eta Square test. t arithmetic (12.976)>t table (58;0.05) is 2.002, then Ho is rejected and Ha is accepted. So, the two classes have different levels of confidence. In other words, there is an influence in learning strategy everyone is a teacher here on students confidence in learning fourth grade mathematics at Pagerwojo Elementary School. And in the eta square test the researchers conclude this research has a very big effect because it shows 1,000 result, if the dependent strategy shows results less than 0.06 then the research shows there is little effect whereas if the results show 0.06-0.14 then the level of influence is moderate, and if it shows results more than 0.14, it has a big effect. So with this research the Effect of the Everyone is a Teacher Here Strategy on Students Confidence in Learning Math Grade IV at Pagerwojo Elementary School, has great influence.